Pengaruh motivasi kerja dan kompensasi terhadap perilaku etis karyawan dalam sistem penggajian dengan gaya kepemimpinan sebagai variabel moderating - Nababan, Daniel (Jurnal Manajemen, 2017)
This research is done to analyze the influence of Work Motivation and Compensation toward Employees’ Ethical Behavior within Payroll System by Utilizing Leadership Style as Moderating Variable. This research used 34 people as sample, who were the employees of PT. Telkom Indonesia Yogyakarta Local Area, with Work Motivation Payroll, and Leadership Style serving as variables. The hypothesis in this researched was tested by using double regression analysis system. The result of this research is that Work Motivation and compensation given brought significant impact in employees’ ethical behavior within the payroll system, that moderation in leadership style brought significant impact within the influence of work motivation and compensation toward employees’ ethical behavior within payroll system, while moderation in leadership style did not brought significant impact within the influence of compensation toward employees’ ethical behavior within payroll system